Balancing adaptability and standardisation: insights from 27 routinely implemented ICHOM standard sets - Leo Benning; Zofia Das-Gupta; Luz Sousa Fialho; Stephanie Wissig; Neo Tapela; Suzanne Gaunt (BMC, 2022)
Abstract Background Healthcare systems around the world experience increasing pressure to control future growth of healthcare expenditures. Among other initiatives, quality and value-based benchmarking has become an important field to inform clinical evaluation and reimbursement questions. The International Consortium for Health Outcomes Measurement (ICHOM) has become one of the driving forces to translate scientific evidence into standardized assessments that are routinely applicable in day-to-day care settings. These aim to provide a benchmarking tool that allows the comparison and competition of health care delivery on the basis of value-based health care principles. Methods This work focuses on the consolidation of the ICHOM methodology and presents insights from 27 routinely implemented Standard Sets. The analysis is based on a literature review of the ICHOM literature repository, a process document review and key informant interviews with ICHOM's outcomes research and development team. Results Key findings are that the scope of ICHOM Standard Sets shifted from a more static focus on burden of disease and poorly standardized care pathways to a more dynamic approach that also takes into account questions about the setting of care, feasibility of implementing a benchmarking tool and compatibility of different Standard Sets. Although certain overlaps exist with other initiatives in the field of patient reported outcomes (PRO), their scopes differ significantly and they hence rather complement each other. ICHOM pursues a pragmatic approach to enable the benchmarking and the analysis of healthcare delivery following the principles of value-based healthcare. Conclusion The ICHOM Standard Sets complement other initiatives in the field of patient-reported outcomes (PRO) and functional reporting by placing a particular focus on healthcare delivery, while other initiatives primarily focus on evaluation of academic endpoints. Although ICHOM promotes a pragmatic approach towards developing and devising its Standard Sets, the definition of standardized decision making processes emerged as one of the key challenges. Furthermore, the consolidation of core metrics across number of disease areas to enable the parallel implementation of different Standard Sets in the same care setting is an important goal that will enable the widespread implementation of patient-reported outcome measures (PROM).